2009
DOI: 10.1089/aid.2009.0062
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Oxidative Stress in HIV-Infected Individuals: A Cross-Sectional Study

Abstract: HIV infection increases the oxidative stress process, and antiretroviral combination therapy increases protein oxidation and preexistent oxidative stress. The latter induces production of reactive oxygen species. Lipid peroxidation (LPO) is a means of determining oxidative stress. There is also a deficiency of glutathione in HIV infection. Persistent oxidative load leads to an accelerated rate of consumption of glutathione (GSH). This study measured LPO and GSH levels in plasma of HIV-infected individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…It has been previously shown that the HIV-infected populations have significantly lower antioxidant concentrations than non-HIV individuals [9,10,13]. Lower non-enzymatic antioxidant concentrations occurred also in HIV patients with diverse neoplastic manifestation [41,42].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been previously shown that the HIV-infected populations have significantly lower antioxidant concentrations than non-HIV individuals [9,10,13]. Lower non-enzymatic antioxidant concentrations occurred also in HIV patients with diverse neoplastic manifestation [41,42].…”
Section: Discussionmentioning
confidence: 96%
“…Consistent changes in redox responsive cascades and in the expressions of corresponding target genes may have a similar or even greater impact on senescence as the direct radical inflicted damage of cellular constituents [9,16].…”
Section: Multivariate Discriminant Analysis Of Redox and Progression mentioning
confidence: 98%
See 1 more Smart Citation
“…The study and enhancement of surrogate markers of HIV disease progression, including OS indexes, continues to be an important area of research particularly with the advent of therapies that claim to halt or slow the process of immunological decline [68][69][70][71][72]. Additional markers and combinatorial analysis that add value to T-CD4+ lymphocyte subset would therefore be useful i.e.…”
Section: Oxidative Stress During Antiretroviral Treatmentmentioning
confidence: 99%
“…In addition, there was a significant positive correlation between absolute CD4 + T cells and GSH levels. However, there was no significant difference in the levels of LPO and GSH among HIV-1 infected individuals receiving antiretroviral therapy (ART) and those without ART (Wanchu et al, 2009). Jordão Júnior et al (1998) evaluated 28 serologically positive HIV-1 patients, 16 patients with AIDS (with < 200/mm 3 CD4 + T lymphocytes) and 12 HIV-1 infected and asymptomatic patients (with 200-500/mm 3 CD4 + T lymphocytes).…”
Section: Evidences Of Oxidative Stress In Individuals Infected With Hmentioning
confidence: 99%